1999
DOI: 10.1021/bc990022e
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-Labeling of Hydrazones of a Hydrazinonicotinamide Conjugated Cyclic Peptide

Abstract: Eight HYNICtide hydrazones (three with aliphatic substituents and five with aromatic groups) were studied for their potential use as the final intermediate for preparation of RP444, a new radiopharmaceutical under development for imaging thrombosis. The goal of this study is to screen various hydrazones through stability testing and radiolabeling and find those which are able to remain stable without significant degradation in the manufacturing process and at the same time are reactive to produce enough free h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 13 publications
0
47
0
Order By: Relevance
“…Since then, the HYNIC technology has successfully been used for the 99m Tc-labeling of antibodies [3][4][5][6][7][8] and small biomolecules (BMs), including chemotactic peptides [9][10][11][12][13][14][15][16][17][18], somatostatin analogs [19][20][21][22][23][24][25],"stealth" liposomes [26,27], antisense oligonucleotides [28][29][30][31], a folate receptor ligand [32], and polypeptides [32][33][34]. A ternary ligand system (HYNIC, tricine, and trisodium triphenylphosphine-3,3¢,3≤-trisulfonate, TPPTS) has been used for the 99m Tc-labeling of chemotactic peptides [35] and leukotriene B 4 (LTB 4 ) receptor antagonists [36][37][38][39] for imaging infection and inflammation, integrin a v b 3 receptor antagonists for tumor imaging [40], and a glycoprotein IIb/IIIa (GPIIb/IIIa) receptor antagonist for imaging thrombosis [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the HYNIC technology has successfully been used for the 99m Tc-labeling of antibodies [3][4][5][6][7][8] and small biomolecules (BMs), including chemotactic peptides [9][10][11][12][13][14][15][16][17][18], somatostatin analogs [19][20][21][22][23][24][25],"stealth" liposomes [26,27], antisense oligonucleotides [28][29][30][31], a folate receptor ligand [32], and polypeptides [32][33][34]. A ternary ligand system (HYNIC, tricine, and trisodium triphenylphosphine-3,3¢,3≤-trisulfonate, TPPTS) has been used for the 99m Tc-labeling of chemotactic peptides [35] and leukotriene B 4 (LTB 4 ) receptor antagonists [36][37][38][39] for imaging infection and inflammation, integrin a v b 3 receptor antagonists for tumor imaging [40], and a glycoprotein IIb/IIIa (GPIIb/IIIa) receptor antagonist for imaging thrombosis [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…Animals were monitored on the gamma camera (PhoGama large field-of-view Anger camera and NucLearMac computer system). Sequential anterior images were collected for 5 min at the specified time (5,15,30,45,60,90 and 120 min) using the 256 × 256 image matrix while animals remained under anesthesia. Upon completion of the experiment, the tumor-bearing mice were sacrificed by sodium pentobarbital overdose (150 -200 mg/kg).…”
Section: Imaging Studiesmentioning
confidence: 99%
“…For the last decade, we have been using ternary ligand systems (HYNIC, tricine, water soluble phosphine or pyridine analog) for 99m Tc-labeling of small biomolecules, including chemotactic peptides [40] and LTB 4 antagonists [41,42] for imaging infection/inflammation, integrin α v β 3 antagonists for tumor imaging [27][28][29][30], and a GPIIb/IIIa antagonist for imaging thrombosis [43][44][45][46]. Regardless of the biomolecule, the Tc:HYNIC:L:tricine ratio in [ 99m Tc(HYNIC-biomolecule)(tricine)(L)] always remains 1:1:1:1 as demonstrated via mixed ligand experiments at the tracer level [43,44], and has been further confirmed by the LC-MS data of [ 99m Tc(HYNIC-biomolecule)(tricine)(L)] (L = TPPTS and ISONIC) at both macroscopic and tracer levels [47,48].…”
Section: Radiochemistrymentioning
confidence: 99%
“…5 During radiolabeling studies, we found that SnCl 2 was not needed if the TPPTS concentration was b 5 mg/mL because TPPTS serves as both a reducing agent and a coligand. Using the non-SnCl 2 formulation, RP444 can be readily prepared by reacting 100 mCi of Na 99m TcO 4 with 20 mg of XV066 in the presence of excess tricine and TPPTS.…”
Section: Synthesis Of Rp444 By a Non-sncl 2 Formulationmentioning
confidence: 99%
“…5 The ideal pH range is 4.0±5.0. In the SnCl 2 formulation, there is very little control over the pH, which may contribute to the large variations in RCP of RP444 and the high failure rate at high activity levels ( !…”
Section: Buffering Agentmentioning
confidence: 99%